2022
DOI: 10.1186/s12916-022-02298-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined impact of lipidomic and genetic aberrations on clinical outcomes in metastatic castration-resistant prostate cancer

Abstract: Background Both changes in circulating lipids represented by a validated poor prognostic 3-lipid signature (3LS) and somatic tumour genetic aberrations are individually associated with worse clinical outcomes in men with metastatic castration-resistant prostate cancer (mCRPC). A key question is how the lipid environment and the cancer genome are interrelated in order to exploit this therapeutically. We assessed the association between the poor prognostic 3-lipid signature (3LS), somatic genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Of note, statins can also alter tryptophan metabolism [ 24 ], either directly through their effects on cholesterol metabolism or indirectly via other targets in cytokine‐producing immune cells. A recent report highlighted the importance of the potential association between elevated circulating sphingolipids with genetic aberrations in metastatic CRPC, such as AR , TP53 and RB1 , and that a biomarker signature combining lipid and genetic abnormalities may be predictive of worse prognosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, statins can also alter tryptophan metabolism [ 24 ], either directly through their effects on cholesterol metabolism or indirectly via other targets in cytokine‐producing immune cells. A recent report highlighted the importance of the potential association between elevated circulating sphingolipids with genetic aberrations in metastatic CRPC, such as AR , TP53 and RB1 , and that a biomarker signature combining lipid and genetic abnormalities may be predictive of worse prognosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analyses of clinical lipidomics publications in 2022 using Scopus search terms “lipidomics” AND “clinic*” on 15 th December 2022 …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
“…Bibliometric analyses of clinical lipidomics publications in 2022 according to separation techniques, detectors, and RPLC columns used …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, atrial fibrillation, frequent premature ventricular contractions, interrupted QTc, and refractory hypokalaemia was reported in an elderly patient with metastatic castra-tion-resistant prostate cancer who received abiraterone [74]. A most recent cell-free DNA sequencing and lipid profile analysis on 106 patients with metastatic castration-resistant prostate cancer who received different chemotherapeutics (e.g., abiraterone acetate and enzalutamide) showed aberrations in the androgen receptor, TP53, RB1, PI3K, and aggressive-variant prostate cancer along with lipid abnormalities [75] are well-known pieces of evidence to be risk factors for cardiovascular disorders [76]. Furthermore, a case report showed that the administration of abiraterone acetate to a 70-year-old male resulted in cardiovascular dysfunction and syncope [77] Similarly, ventricular repolarization is reported as a possible adverse effect of enzalutamide therapy in male patients with hypogonadism [88].…”
Section: Cardiotoxicity Of Second-generation Anti-androgensmentioning
confidence: 99%